Applied Ethics in the Fractured State - Grant, Bligh; Drew, Joseph (Writer on public policy and governance); Christensen, Helen E. (Research in ethical issues in organizations, 2018)
This book brings together the refereed proceedings of the 24th Annual Conference of the Australian Association of Professional and Applied Ethics (AAPAE) 'Applied Ethics in the Fractured State', held at the Institute for Public Policy and Governance, University of Technology Sydney in June 2017.